2020
DOI: 10.1007/s11095-020-02912-x
|View full text |Cite
|
Sign up to set email alerts
|

A Biopredictive In Vitro Approach for Assessing Compatibility of a Novel Pediatric Hydrocortisone Drug Product within Common Pediatric Dosing Vehicles

Abstract: Purpose The objective of the present work was to screen whether a novel pediatric hydrocortisone granule formulation can be co-administered with common food matrices and liquids. Methods Pediatric hydrocortisone granules were studied using a biopredictive in vitro approach. Experiments included an in situ chemical compatibility study of active ingredient and drug product with liquid dosing vehicles and soft foods commonly ingested by infants, pre-school- and school children. Drug solubility and stability exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 21 publications
(30 reference statements)
2
12
0
Order By: Relevance
“…The impurity assay showed that impurity B (cortisone) and G (hydrocortisone-21-aldehyde) were found after 120 days of storage. This observation was similar to the findings reported by Wollmer et al [ 17 ]. They have also found small concentrations of impurity B and G, all of which were lower than the USP and EP limits.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…The impurity assay showed that impurity B (cortisone) and G (hydrocortisone-21-aldehyde) were found after 120 days of storage. This observation was similar to the findings reported by Wollmer et al [ 17 ]. They have also found small concentrations of impurity B and G, all of which were lower than the USP and EP limits.…”
Section: Discussionsupporting
confidence: 93%
“…Although several stakeholders have already expressed their support in developing pediatric formulations [ 25 , 26 , 27 , 28 , 29 , 30 , 31 ], an urgent need exists to improve the standardization in compounded enteral formulations to increase the safety and compliance of preparations made in Japan. To date, most tested hydrocortisone formulations for pediatric patients are liquids [ 17 , 32 ]; however, the stability and safety of solid oral compounded products have not been reported, except for hydrocortisone mini-tablet forms [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Sprinkling medication onto food can alter its pharmacokinetic characteristics. To demonstrate hydrocortisone granules in capsules for opening compatibility with child appropriate fluids and soft foods; in vitro and in vivo studies were conducted [52][53][54]. In vitro data and modeling confirmed that pediatric patient exposure to hydrocortisone from the granules is unlikely to be impacted by co-administration with water, breast, cow or formula milk, orange, apple or tomato juice, or soft foods such as apple sauce or yogurt.…”
Section: Clinical Study Datamentioning
confidence: 99%